Design and Development of Automated Swarm Robots - N, Nagendra Kumar; M, Sheethal C; S, Supriya Jude; M, Suresh; B, Chaithra (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2017)
Autonomous robots are programmable mechanical devices, which interact with the environment and can perform tasks without the aid of human interaction. Today most of the robots are used to repetitive actions, which are considered too dangerous for humans. They perform tasks in hostile environments, by carrying out tasks with speed and accuracy. Swarm robotics is an approach to the co-ordination of multirobot system, which consists of large number of simple physical robots. It is inspired by the emergent behaviour observed in social insects called Swarm Intelligence. Here is the one application which involves the concept of autonomous robots and swarm intelligence. It consists of master robot which tracks the path using IR sensor and even controls the action of slave robots through RF communication. Swarm robots travel from source to destination by avoiding the obstacles through the path using ultrasonic sensor. The individual robots are controlled using the microcontroller ATMEGA328P. It has many applications in agriculture, disaster management and military.